Trends in Digital Twin Technology for Industry 4.0: A Bibliometric Study - Judijanto, Loso; Qadriah, Laila; Prabowo, Iwan Ady; Widyatmoko, Widyatmoko; Sabila, Puji Chairu (Eastasouth Institute, 2024)
Digital Twin (DT) technology has emerged as a critical enabler of Industry 4.0, bridging the physical and digital worlds through real-time data integration, simulation, and optimization. This study conducts a comprehensive bibliometric analysis to explore the research trends, key contributors, and thematic clusters in DT research over the past decade. The analysis reveals China's leading role in DT research, supported by strong international collaborations with the United States, Germany, and other countries. Key themes include technological enablers such as IoT, sensors, and infrastructure, as well as emerging applications in sustainability, smart cities, and energy systems. Challenges such as risks, uncertainties, and feasibility constraints remain significant barriers to DT adoption, highlighting the need for interdisciplinary collaboration and standardization efforts. The study identifies opportunities for integrating DT with technologies like blockchain and AI, as well as expanding applications in healthcare and agriculture. These findings provide valuable insights for researchers, practitioners, and policymakers to advance DT technology and its transformative potential in Industry 4.0.